2002
DOI: 10.1046/j.1470-6431.2002.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic purchasing motivations and attitudes: are they ethical?

Abstract: Despite the increased documentation of consumers’ purchases of organic food products, the motivations for such purchases are relatively under‐researched. An individual’s choice of food products can be linked clearly to ethical stances, but ethical choices can also vary from individual to individual, from industry to industry and among countries. Consequently, this paper investigates the degree to which ethical beliefs influence Scottish consumer perceptions, beliefs, attitudes and purchasing decisions, with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
196
5
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(228 citation statements)
references
References 7 publications
9
196
5
5
Order By: Relevance
“…The findings are similar to many previous studies, including organic food healthier (Brennan and Kuri 2002;Grankvist andBiel 2001), tastier (McEachern andMcClean 2002;Kihlberg and Risvik 2007), safer and more environmentally friendly (Yiridoe et al 2005), but shorter shelf life (Magnusson 2004) andexpensive(O'Donovan andMcCarthy 2002).…”
Section: Discussionsupporting
confidence: 91%
“…The findings are similar to many previous studies, including organic food healthier (Brennan and Kuri 2002;Grankvist andBiel 2001), tastier (McEachern andMcClean 2002;Kihlberg and Risvik 2007), safer and more environmentally friendly (Yiridoe et al 2005), but shorter shelf life (Magnusson 2004) andexpensive(O'Donovan andMcCarthy 2002).…”
Section: Discussionsupporting
confidence: 91%
“…As a specific example, McEachern and McClean [116] found that among those who had never purchased organic dairy products, the main deterrent was pricing constraints. However, as Holdsworth [67] noted, such assumptions are not necessarily based upon experience or accurate information, a point relevant to all perceptions relating to logistical factors.…”
Section: Determining Factorsmentioning
confidence: 99%
“…Uninformed and unreflective consumers apply a hedonistic, materialistic-oriented ethic in relation to the purchasing of organic products (McEachern and McClean 2002, Meeusen et al 2003, Aertsens et al 2009). They are not http://www.ecologyandsociety.org/vol19/iss4/art5/ particularly interested in organic or the wider impacts of organic production beyond the product, and do not feel responsible for the impact of their purchasing behavior.…”
Section: Ethics Within Concepts Of Reflexivitymentioning
confidence: 99%